IMPLEMENTATION OF THE VILLAGE INFORMATION SYSTEM (SID) IN REALIZING PUBLIC INFORMATION DISCLOSURE (STUDY ON THE WEBSITE OF THE SEMAMBUNG VILLAGE GOVERNMENT, WONOAYU DISTRICT, SIDOARJO REGENCY) - Asrori, Maya Dinul; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study is to describe and analyze the implementation of the village information system (SID) in realizing public information disclosure in Semambung Village, Wonoayu District, Sidoarjo Regency. The analysis was carried out using the theoretical framework of George C. Edward III's policy implementation which included aspects of communication, resources, disposition, and bureaucratic structure. Methods: This study uses a qualitative method with a descriptive approach. Data was collected through interviews with village officials, field observations, and documentation review related to the management of village websites as a means of information disclosure. Data analysis is carried out through the process of data reduction, data presentation, and conclusion drawn. Results: The results of the study show that from the communication aspect, socialization related to SID is not even because it relies more on social media. In terms of resources, website management is still handled by one operator without special training support or adequate budget allocation. In terms of disposition, operators show a positive commitment even though they have not received adequate incentives and institutional support. Meanwhile, from the aspect of bureaucratic structure, there is no clear SOP or division of tasks so that implementation still depends on individual initiatives. With these various obstacles, SID has been proven to increase access to public information and encourage community participation, which is reflected in a significant increase in the number of visitors to the village website. Novelty: The novelty lies in the analysis of the implementation of SID at the village level that highlights technical and institutional constraints in more detail. These findings contribute to the development of literature on digital-based public information governance in villages as well as serve as a basis for evaluation to strengthen apparatus capacity, institutional support, and the formulation of more targeted SOPs to optimize the implementation of SID.